2020
DOI: 10.5114/wiitm.2020.100714
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with minimally invasive treatment of pilonidal sinus in children.

Abstract: Introduction Sinus pilonidalis (SP) is an acquired inflammatory disease, which is relatively common in the paediatric population. Surgery is indicated in symptomatic patients. In 2017, minimally invasive pilonidal sinus treatment (EPSiT) was adapted to the paediatric population. Aim To evaluate the first experience with minimally invasive endoscopic treatment of SP (PEPSiT) in children and adolescents in the Czech Republic. Material and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Moreover, the endoscopic surgery has been used for the acute pilonidal abscess treatment 30 , 39 , 40 with reduced postoperative pain, lower duration of wound healing and time off work as shown by two comparative studies. 30 , 39 Similar results have been obtained by paediatric surgeons such as Esposito et al 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 achieving low postoperative pain, short length of hospital stay and better outcomes than open technique.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the endoscopic surgery has been used for the acute pilonidal abscess treatment 30 , 39 , 40 with reduced postoperative pain, lower duration of wound healing and time off work as shown by two comparative studies. 30 , 39 Similar results have been obtained by paediatric surgeons such as Esposito et al 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 achieving low postoperative pain, short length of hospital stay and better outcomes than open technique.…”
Section: Discussionsupporting
confidence: 79%
“…Several non-comparative reports have demonstrated similar results, with a recurrence rate ranging from 0 to about 6% ( 32 , 34 38 , 40 , 41 ). In this setting, several authors considered the PEPSiT as the gold standard of care in cases of PSD in the pediatric population.…”
Section: Discussionmentioning
confidence: 52%
“…Esposito et al adapted EPSIT to the pediatric population as PEPSIT (pediatric EPSIT) and presented it in 2018 [16]. Dotlacil et al reported one of the largest series on PEPSIT, in which they achieved 87% healing after the first PEPSIT and confirmed minimal invasiveness, short hospital stay, and low requirement of analgesics [15].…”
Section: Discussionmentioning
confidence: 99%
“…These methods promise shorter wound healing time and time to return to work, and improved pain control and cosmesis. Endoscopic procedures can also be used in adolescent patients, and these methods also reduce the sense of embarrassment that patients experience [ 14 , 15 ]. EPSIT is a minimally invasive method described by Meinero et al [ 2 ].…”
Section: Discussionmentioning
confidence: 99%